Established and emerging lipid-lowering drugs for primary and secondary cardiovascular prevention: leading article - Michaeli, Daniel; Michaeli, Julia; Albers, Sebastian; Boch, Tobias; Michaeli, Christoph T. (American journal of cardiovascular drugs, 2023)
Despite treatment with statins, patients with elevated low-density lipoprotein cholesterol (LDL-C) and triglycerides remain at increased risk for adverse cardiovascular events. Consequently, novel pharmaceutical drugs have been developed to control and modify the composition of blood lipids to ultimately prevent fatal cardiovascular events in patients with dyslipidaemia. This article reviews established and emerging lipid-lowering drugs regarding their mechanism of action, development stage, ongoing clinical trials, side effects, effect on blood lipids and reduction in cardiovascular morbidity and mortality. We conducted a keyword search to identify studies on established and emerging lipid modifying drugs. Results were summarized in a narrative overview. Established pharmaceutical treatment options include the Niemann-Pick-C1 like-1 protein (NPC1L1) inhibitor ezetimibe, the protein convertase subtilisin-kexin type 9 (PCSK9) inhibitors alirocumab and evolocumab, fibrates as peroxisome proliferator receptor alpha (PPAR-α) activators, and the omega-3 fatty acid icosapent ethyl. Statins are recommended as the first-line therapy for primary and secondary cardiovascular prevention in patients with hypercholesterinaemia and hypertriglyceridemia. For secondary prevention in hypercholesterinaemia, second-line options such as statin add-on or statin-intolerant treatments are ezetimibe, alirocumab and evolocumab. For secondary prevention in hypertriglyceridemia, second-line options such as statin add-on or statin-intolerant treatments are icosapent ethyl and fenofibrate. Robust data for these add-on therapeutics in primary cardiovascular prevention remains scarce. Recent biotechnological advances have led to the development of innovative small molecules (bempedoic acid, lomitapide, pemafibrate, docosapentaenoic and eicosapentaenoic acid), antibodies (evinacumab), antisense oligonucleotides (mipomersen, volanesorsen, pelcarsen, olezarsen), small interfering RNA (inclisiran, olpasiran), and gene therapies for patients with dyslipidemia. These molecules specifically target new cellular pathways, such as the adenosine triphosphate-citrate lyase (bempedoic acid), PCSK9 (inclisiran), angiopoietin-like 3 (ANGPTL3: evinacumab), microsomal triglyceride transfer protein (MTP: lomitapide), apolipoprotein B-100 (ApoB-100: mipomersen), apolipoprotein C-III (ApoC-III: volanesorsen, olezarsen), and lipoprotein (a) (Lp(a): pelcarsen, olpasiran). The authors are hopeful that the development of new treatment modalities alongside new therapeutic targets will further reduce patients’ risk of adverse cardiovascular events. Apart from statins, data on new drugs’ use in primary cardiovascular prevention remain scarce. For their swift adoption into clinical routine, these treatments must demonstrate safety and efficacy as well as cost-effectiveness in randomized cardiovascular outcome trials.